Pembangunan Aplikasi Senaman Pemula Calisthenics - Mohammad Hazly Hakiki Mohd Azize,; Suhaila Mohd Yasin, (Applied Information Technology And Computer Science, 2021)
The Beginner Calisthenics Exercise Application is an application that shows you how to do a calisthenics exercise routine. When the world is hit by the Novel Coronavirus 2019 pandemic (Covid-19) everyone is affected by this dangerous virus, many want to stay healthy and fit at home but do not know how to start training and exercise at home. Therefore, an application titled "Calisthenics Beginner Apps" will be developed in this project. This application was developed to help users who want to practice healthy living activities but cannot leave home and do not have appropriate exercise tools. The project develops a "Mobile" exercise application to attract and facilitate users to stay active, healthy and fit at home at any time. The model used in the development of this application is the ADDIE Model as it is compatible with the development of the system in the current phase. The system was also developed using Android Studio and Flutter software as encoding, and xampp as a database as well as a system server. Finally, it is expected that the Beginner Calisthenics Exercise Application system will benefit consumers as it helps to create and operate a healthy lifestyle.